0
$\begingroup$

How can I prove that:

$$\sum_{m\geq n}^\infty \frac{(\lambda (1-p)t)^m}{(m-n)!}=((1-p)\lambda t)^n e^{(1-p)\lambda t}$$

$\endgroup$
  • $\begingroup$ The left side not even defined. $\endgroup$ – Kavi Rama Murthy Nov 13 '18 at 9:07
  • $\begingroup$ @KaviRamaMurthy Better now? $\endgroup$ – Dole Nov 13 '18 at 9:18
  • $\begingroup$ Perhaps the denominator is $(m - n)!$. $\endgroup$ – Awe Kumar Jha Nov 13 '18 at 9:28
  • $\begingroup$ Is $n$ a free choice, or should you be considering $\sum_n \sum_{m \geq n} \ldots$? $\endgroup$ – Kevin Nov 13 '18 at 9:28
5
$\begingroup$

I am interpreting $m-n!$ as $(m-n)!$. Just change the variable from $m$ to $j=m-n$. Let $x=\lambda (1-p)t$. You will get $\sum_{j=1}^{\infty} \frac {x^{j+n}} {j!}$. Pull out $x^{n}$ and use the series for $e^{x}$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.